2023
DOI: 10.3389/fphar.2023.1303844
|View full text |Cite
|
Sign up to set email alerts
|

Drug repositioning in thyroid cancer treatment: the intriguing case of anti-diabetic drugs

Alessia Greco,
Francesca Coperchini,
Laura Croce
et al.

Abstract: Cancer represents the main cause of death worldwide. Thyroid cancer (TC) shows an overall good rate of survival, however there is a percentage of patients that do not respond or are refractory to common therapies. Thus new therapeutics strategies are required. In the past decade, drug repositioning become very important in the field of cancer therapy. This approach shows several advantages including the saving of: i) time, ii) costs, iii) de novo studies regarding the safety (just characterized) of a drug. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 184 publications
0
3
0
Order By: Relevance
“… 105 It is worth noting that the use of thiazolidinediones in diabetic patients is declining significantly and is even almost completely removed from the market. 106 , 107 Studies have revealed that activated PPARγ can inhibit tumorigenesis through anti-angiogenic and anti-inflammatory effects and can also control the tumor microenvironment by regulating the function of tumor cells, ultimately playing a role in resisting tumor metastasis. 108 , 109 Lv et al reported that rosiglitazone and pioglitazone can inhibit the PI3K/PKB signaling pathway by activating PPARγ, thereby inducing cell cycle G2 arrest and apoptosis of the bladder cancer cells, ultimately inhibiting cell proliferation in vitro and tumor cell growth in vivo.…”
Section: Anti-thyroid Cancer Effects Of Some Hypoglycemic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“… 105 It is worth noting that the use of thiazolidinediones in diabetic patients is declining significantly and is even almost completely removed from the market. 106 , 107 Studies have revealed that activated PPARγ can inhibit tumorigenesis through anti-angiogenic and anti-inflammatory effects and can also control the tumor microenvironment by regulating the function of tumor cells, ultimately playing a role in resisting tumor metastasis. 108 , 109 Lv et al reported that rosiglitazone and pioglitazone can inhibit the PI3K/PKB signaling pathway by activating PPARγ, thereby inducing cell cycle G2 arrest and apoptosis of the bladder cancer cells, ultimately inhibiting cell proliferation in vitro and tumor cell growth in vivo.…”
Section: Anti-thyroid Cancer Effects Of Some Hypoglycemic Drugsmentioning
confidence: 99%
“…105 It is worth noting that the use of thiazolidinediones in diabetic patients is declining significantly and is even almost completely removed from the market. 106,107 Studies have revealed that activated PPARγ can inhibit tumorigenesis through anti-angiogenic and antiinflammatory effects and can also control the tumor microenvironment by regulating the function of tumor cells, ultimately…”
Section: Anti-thyroid Cancer Effects Of Some Hypoglycemic Drugs Thiaz...mentioning
confidence: 99%
“…The enhancement of cytotoxicity for specific drugs can be achieved through the induction of autophagy. Experimental evidence has shown that AC effectively induces hepatic autophagy in mice by modulating the phosphorylation levels of upstream proteins, such as PI3K, AKT, mTOR, 70S6K, and 4EBP-1 ( Greco et al, 2023 ).…”
Section: Toxicitymentioning
confidence: 99%